Quality of ras cheese made by probiotic strain of Lactobacillus rhamnosus - Kebary, K. M. K.; Yousef, Iman T. A.; El-Shazly, Hoida A. M.; Rajab, W. A. A. (2011)
Five ras cheese treatments were made by replacing normal cheese starter with lactobacillus rhamnosus. Cheese treatments were microbiologically, chemically and organoleptically evaluated when fresh and after 1,2,3 and 4 months. Moisture content decreased, while total nitrogen, fat, ash, titratable acidity, soluble nitrogen, total volatile fatty scids.
Includes references.
Summary in Arabic.
1
Keywords: Cheese -- Quality; Cheese -- Varieties; Cheesemaking; Fatty acids in human nutrition